Behaviour of Cold Formed Steel Built-Up Channel Columns Strengthened Using CFRP - Naganathan S.; Chakravarthy H.G.N.; Anuar N.A.; Kalavagunta S.; Mustapha K.N.B. (Korean Society of Steel Construction, 2023)
Carbon fiber reinforced plastics; Carbon fibers; Failure modes; Steel beams and girders; Studs (structural members); Buckling strength; Carbon fibre reinforced polymer; Channel columns; Cold-formed steel; Coupon tests; Lateral displacements; Test specimens; Ultimate loads; Steel fibers